Fuel not food—towards sustainable utilization of gutter oil. Issue 3 (4th May 2017) - Karmee, Sanjib Kumar
ABSTRACT: Waste cooking oil is discarded into sewage and waste bins in various developing countries. In China, the discarded oil is scooped illegally from drains by smugglers. After collection, the obtained waste oil is reprocessed; the resulting substance is popularly called gutter oil. Gutter oil and its mixture with fresh vegetable oils are sold in food markets at lower prices. This created panic among the general public because of food safety concerns. 1 H NMR (proton nuclear magnetic resonance), MALDI-MS (matrix-assisted laser desorption/ionization-mass spectrometry) and HPLC (high-performance liquid chromatography) are used for the detection of gutter oil. Currently, sustainable utilization of gutter oil for biofuel production is being explored using chemical and enzymatic methods. Furthermore, trial runs by Boeing company shows that gutter oil can be blended with normal jet fuel for use in aviation industry. Annually, around 1.8 billion L (476 million gallons) of biofuels can be produced from gutter oil in China.